Exploring Wheat Farmers’ Soil Health Management Practices, Adoption Characteristics, and Information Preferences - Maureen Victoria; Holli Leggette; Jamie Foster; Morgan Orem; Clark Neely; Haly Neely; Karissa Palmer (Journal of Applied Communications, 2025)
Healthy soil is critical to feeding and sustaining healthy human and animal populations and ensuring the land is productive for years to come, yet farmers often hesitate to adopt soil health management practices despite their benefits. This highlights a need for education and targeted communication strategies to encourage adoption. Our qualitative study aimed to explore soil health management practices of wheat farmers in Texas, Oklahoma, and Louisiana. We conducted semi-structured interviews with 32 farmers to determine their soil health management practices, adoption characteristics, and information and communication preferences. We found farmers describe healthy soil three ways: healthy soil is a living biome, healthy soil has texture and structure, and healthy soil is a costly responsibility. The farmers managed soil health using tillage methods and technology implementation (e.g., heavy equipment, soil testing, fertilizing) and managed soil health to preserve the land for future generations, control erosion, and improve their bottom line. Wheat farmers choose to adopt or reject soil health management practices: long-term benefits of soil fertility, financial, climatological and environmental, information from neighbors, traditional, and functionality and necessity. Farmers preferred to receive information from Extension specialists, university faculty, and crop consultants as well as themselves. In addition, extension-sponsored field days and demonstrations were farmers’ most preferred communication mediums. Our findings inform programming focused on scientific principles of soil and soil, on how farmers can know when they have reached the scientific pinnacles of healthy soil, and on perspectives and achievements of peers who possess expertise in soil health practices.
Keywords: communication; adoption; innovation; soil; conservation